Keterkaitan Koneksi Politik terhadap Agresivitas Pajak dengan Good Corporate Governance Sebagai Variabel Moderasi (Studi Pada Perusahaan Tambang yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Vidiyanna Rizal Putri (STIE Indonesia Banking School, 2018)
The purpose of this study is to examine the relationship between a political connection and tax aggesiveness with proxied through Cash Effective Tax Rate (CETR) and also see the institutional ownership to the relationship between connection political and tax aggressiveness with the capital intensity and firm size as control variables. This research was conducted on mining firms in Indonesia Stock Exchange (IDX) 2012 2016. Data obtained by accessing the Indonesia Stock Exchange’s website. The samples in this study used purposive sampling technique in order to get a sample size of 18 companies and the number of observations is 65. The results of this study indicate that the connection political affect tax avoidance. Institutional ownership as a moderating variable did not affect the relationship between the political connection and tax avoidance. While capital intensity also not affect on tax avoidance and firm size effect on tax avoidance.